Pengaruh Lingkungan Teman Sebaya Terhadap Motivasi Belajar Matematika SiswaDevelopment Research, Teacher Competency, Research, Modified Model - Elinggrawati Elinggrawati; Tasnim Rahmat; Wedra Aprison; Haida Fitri (Peneliti.net, 2023)
This research is motivated by the results of observations where it is seen that the students' low motivation to learn mathematics is influenced by the peer environment. The formulation of the research problem is